2011
DOI: 10.1038/hdy.2011.9
|View full text |Cite
|
Sign up to set email alerts
|

Early evolution in a hybrid swarm between outcrossing and selfing lineages in Geum

Abstract: Although often considered as evolutionary dead ends, selfing taxa may make an important contribution to plant evolution through hybridization with related outcrossing lineages. However, there is a shortage of studies examining the evolutionary dynamics of hybridization between outcrossing and selfing taxa. On the basis of differential pollinator attractiveness, production and competitive ability of pollen, as well as levels of inbreeding depression, we predict that the early products of hybridization between o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
57
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 40 publications
13
57
1
Order By: Relevance
“…It could not be explained by differences in phenology (Milne and Abbott, 2008) because both species flower at the same time, but studies on this are needed. Rusham et al (2011) reported a similar result in a hybrid swarm of Geum rivale and G. urbanum, where none of the individuals in the hybrid swarm identified by NEWHYBRIDS were classified as a backcross to G. urbanum. Hybrids between Cardamine enneaphyllos and C. glandulifera were placed by PCR-RFLP analysis in an intermediate position but they also largely overlapped with one of the parental species (Lihová et al, 2007).…”
Section: Discussion Hybrid Status Of Aconitum Populations and Individsupporting
confidence: 56%
“…It could not be explained by differences in phenology (Milne and Abbott, 2008) because both species flower at the same time, but studies on this are needed. Rusham et al (2011) reported a similar result in a hybrid swarm of Geum rivale and G. urbanum, where none of the individuals in the hybrid swarm identified by NEWHYBRIDS were classified as a backcross to G. urbanum. Hybrids between Cardamine enneaphyllos and C. glandulifera were placed by PCR-RFLP analysis in an intermediate position but they also largely overlapped with one of the parental species (Lihová et al, 2007).…”
Section: Discussion Hybrid Status Of Aconitum Populations and Individsupporting
confidence: 56%
“…Intercrossing success (i.e., the production of viable seeds) is also known to be affected by the direction of crossing (28,29). The interplay between these preand/or postzygotic processes can result in unequal transfer of parental genetic material into the genome of hybrid progeny (28,29). Whereas the short-term demographic consequence of this asymmetry is facilitation of establishment, the long-term outcome can be species replacement as we see in Cakile species.…”
Section: Resultsmentioning
confidence: 92%
“…Pollinators rarely commit to random foraging bouts but rather discriminate among plant types (27); such behavior can result in assortative mating and produce the required asymmetry. Intercrossing success (i.e., the production of viable seeds) is also known to be affected by the direction of crossing (28,29). The interplay between these preand/or postzygotic processes can result in unequal transfer of parental genetic material into the genome of hybrid progeny (28,29).…”
Section: Resultsmentioning
confidence: 99%
“…An expected consequence is aberrant endosperm development upon hybridization across mating systems [72]. There is some support for this hypothesis [72], and it may contribute to patterns of elevated pollen gene flow from outcrossing to selfing lineages [73,74]. However, more microevolutionary studies addressing the extent and nature of post-zygotic isolation among selfing and outcrossing populations are needed to better understand the interplay between genomic conflicts, mating systems and reproductive isolation.…”
Section: Rspbroyalsocietypublishingorg Proc R Soc B 280: 20130133mentioning
confidence: 99%